2006
DOI: 10.1111/j.1365-2141.2006.06439.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of follicular lymphoma to diffuse large B‐cell lymphoma proceeds by distinct oncogenic mechanisms

Abstract: Summary This study was undertaken to further elucidate the biological mechanisms underlying the frequent event of transformation of follicular lymphoma (FL) to diffuse large B‐cell lymphoma (t‐FL). The gene expression profiles of 20 paired lymph node biopsies, derived from the same patient pre‐ and post‐transformation, were analysed using the Lymphochip cDNA microarray. TP53 mutation analysis was performed and copy number alterations at the c‐REL and CDNK2A examined. Immunohistochemistry was performed on an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 51 publications
7
119
0
1
Order By: Relevance
“…It suggests that deletion of 1p36 may predispose patients to subsequent transformations with high proliferation rate, as described by Davies et al and Lossos et al, rather than lower proliferative transformations. 41,42 Deletion of 6q is detected frequently in acute lymphoblastic leukemia, chronic lymphocytic leukemia, multiple myeloma, DL-BCL, and FL. 32,43 Different studies have shown various regions to be involved; however, only 1 of these has focused specifically on FL in which a 2.3-Mb region of deletion was identified at 6q16.3 in approximately 15% FL cases.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that deletion of 1p36 may predispose patients to subsequent transformations with high proliferation rate, as described by Davies et al and Lossos et al, rather than lower proliferative transformations. 41,42 Deletion of 6q is detected frequently in acute lymphoblastic leukemia, chronic lymphocytic leukemia, multiple myeloma, DL-BCL, and FL. 32,43 Different studies have shown various regions to be involved; however, only 1 of these has focused specifically on FL in which a 2.3-Mb region of deletion was identified at 6q16.3 in approximately 15% FL cases.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the DLBCL cases, these cases are commonly thought to represent transformed disease and therefore may harbor a non-IG-MYC breakpoint or additional translocations (for example, involving BCL2 or CCND1), as well as a higher number of numerical aberrations. [47][48][49][50] Indeed, the complexity score was much higher in the other B-NHL cases (Figure 4a; significance of difference Po0.0001) and gains of 7, 11p, 11q11-22, 12, 18 and X and loss of 4q, 6q13-27, 9, 10p, 15, 17p13 and 17q11-23 were more common compared with the BL core subset ( Figure 5). In addition, patients were older (mean 50 versus 23.5 years, Po0.0001; Figure 2), and the male/female ratio was lower (Supplementary Table 3).…”
Section: The Cytogenetic Profile Of the Bl Core Subset Is Different Fmentioning
confidence: 96%
“…5 In recent studies, genomic changes have been revealed to occur during the transformation from follicular lymphoma to diffuse large B-cell lymphoma. 18,19 In Patient #2, additional nucleotide changes could have developed in the immunoglobulin heavy chain gene of lymphoma cells of the same clonal origin in the 16-year process of the transformation from follicular lymphoma to diffuse large Bcell lymphoma. 5 The goal of this study is to document the fact that orbital lymphomas occur as a recurrence of systemic lymphomas which have initially developed 16 years previously.…”
Section: Discussionmentioning
confidence: 99%